2012
DOI: 10.1073/pnas.1208916109
|View full text |Cite
|
Sign up to set email alerts
|

The role of intracellular calcium phosphate in osteoblast-mediated bone apatite formation

Abstract: Mineralization is a ubiquitous process in the animal kingdom and is fundamental to human development and health. Dysfunctional or aberrant mineralization leads to a variety of medical problems, and so an understanding of these processes is essential to their mitigation. Osteoblasts create the nano-composite structure of bone by secreting a collagenous extracellular matrix (ECM) on which apatite crystals subsequently form. However, despite their requisite function in building bone and decades of observations de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
409
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 475 publications
(426 citation statements)
references
References 33 publications
16
409
0
1
Order By: Relevance
“…In native bone tissue, the structural integrity of bone is a tightly regulated process controlled by coordinated mechanism of collagen synthesis by osteoblasts and their subsequent mineralisation by poorly crystalline HA [45]. The crystal morphology of needle-like nanocrystals obtained on fibroin in our study was similar to the dimensions found on collagen-HA, as…”
Section: Discussionsupporting
confidence: 69%
“…In native bone tissue, the structural integrity of bone is a tightly regulated process controlled by coordinated mechanism of collagen synthesis by osteoblasts and their subsequent mineralisation by poorly crystalline HA [45]. The crystal morphology of needle-like nanocrystals obtained on fibroin in our study was similar to the dimensions found on collagen-HA, as…”
Section: Discussionsupporting
confidence: 69%
“…Metabolomics analysis of differentiated MSC proved that glycolytic induction of lactate production is lowered; whereas, the amount of mitochondrial TCA intermediates such as citrate derived from oxidative metabolism are increased 19. A novel model for bone apatite formation proposed that calcium and phosphorus‐containing mineral aggregates in osteoblast mitochondria, transports via vesicles to the ECM and then converts to more crystalline 9. Interestingly, we determined that accumulation of citrate precipitation was closely associated with calcium deposition and ZIP1‐mediated Zn 2+ influx during osteogenesis (Figures 1, 4, and 5).…”
Section: Discussionmentioning
confidence: 99%
“…(35) In both endochondral ossification and matrix mineralization, however, it seems likely that an initial phase of amorphous mineral deposition precedes the formation of more highly organized mineral. (36,37) Bone mineralization in OI In most cases of OI, mineralization processes seem to be in place and normally functioning. Two exceptions, however, may be the types V and VI OI initially identified as having distinct bone histological appearances (type V mesh-like under polarized light; type VI osteomalacic) at the level of light microscopy.…”
Section: Mineralization Of Bone Matrixmentioning
confidence: 99%